Mambalgin-2 Inhibits Lung Adenocarcinoma Growth and Migration by Selective Interaction With ASIC1/α-ENaC/γ-ENaC Heterotrimer - Sudarikova, Anastasia V.; Bychkov, Maxim L.; Kulbatskii, Dmitrii S.; Chubinskiy-Nadezhdin, Vladislav I.; Shlepova, Olga V.; Shulepko, Mikhail A.; Koshelev, Sergey G.; Kirpichnikov, Mikhail P.; Lyukmanova, Ekaterina N. (Frontiers in Oncology, 2022)
Lung cancer is one of the most common cancer types in the world. Despite existing treatment strategies, overall patient survival remains low and new targeted therapies are required. Acidification of tumor microenvironment drives growth and metastasis of many cancers. Acid sensors such as acid-sensing ion channels ASICs may become promising targets for lung cancer therapy. Previously we showed than inhibition of the ASIC1 channels by recombinant analogue of mambalgin-2 from Dendroaspis polylepis controls oncogenic processes in leukemia, glioma, and melanoma cells. Here, we studied effects and molecular targets of mambalgin-2 in lung adenocarcinoma A549 and Lewis cells, lung transformed WI-38 fibroblasts, and lung normal HLF fibroblasts. We found that mambalgin-2 inhibits the growth and migration of A549, metastatic Lewis P29 cells, and WI-38 cells, but not of normal fibroblasts. A549, Lewis, and WI-38 cells expressed different ASIC and ENaC subunits, while normal fibroblasts did not at all. Mambalgin-2 induced G2/M cell cycle arrest and apoptosis in lung adenocarcinoma cells. In line, acidification-evoked inward currents were observed only in A549 and WI-38 cells. Gene knock-down showed that anti-proliferative and anti-migratory activity of mambalgin-2 is dependent on the expression of ASIC1a, α-ENaC, and γ-ENaC. Using affinity extraction and immunoprecipitation, mambalgin-2 targeting of ASIC1a/α-ENaC/γ-ENaC heteromeric channels in A549 cells was shown. Electrophysiology studies in Xenopus oocytes revealed that mambalgin-2 inhibits the ASIC1a/α-ENaC/γ-ENaC channels with higher efficacy than the ASIC1a channels, pointing on the heteromeric channels as a primary target of the toxin in cancer cells. Finally, bioinformatic analysis showed that increased expression of ASIC1 and γ-ENaC correlates with worse survival prognosis for patients with lung adenocarcinoma. Thus, the ASIC1a/α-ENaC/γ-ENaC heterotrimer can be considered marker of cell oncogenicity and its targeting is promising for design of new selective cancer therapeutics.